Monitoring Earth using SDR Earth Imager. (1st September 2022) - Sharif, Radwan; Tanyer, S. Gokhun; Harrison, Stephen; Driessen, Peter; Herring, Rodney
Abstract: To obtain information about Earth disturbances to the ionosphere of the atmosphere, a Software Defined Radio (SDR) Earth Imager was constructed at the Dominion Radio Astrophysical Observatory (DRAO). This imager used radio waves reflected from the Earth's ionization layer to phase image waves on/in the ionosphere. Two sets of waves were found, one having a constant frequency and another having a large spike. The constant frequency waves represent a continuously active ionospheric disturbance such as a power generating station. The large spike waves were randomly occurring outliers. Candidates for the spike waves are lightning strikes and/or earthquakes. Having the capability to detect these waves opens up the possibility of measuring the power, energy and location of their disturbance. Highlights: The SDR Earth Imager comprises Software Defined Radio (SDR), GPS timers, and an antenna array to detect and monitor the waves existing on the ionosphere. This device using radio waves as the diagnostic carrier wave was constructed and demonstrated enabling two types of phase images, one constant and the other outliers, to be observed. The device is able to provide new information about Earth disturbing events.